1994
DOI: 10.1152/jappl.1994.76.6.2621
|View full text |Cite
|
Sign up to set email alerts
|

Doppler evaluation of cardiac filling and ejection properties in humans during parabolic flight

Abstract: The cardiac filling and ejection properties of seven normal human subjects were examined during microgravity created on a National Aeronautics and Space Administration aircraft during parabolic flight. Doppler echocardiography was used to measure intracardiac velocities in sitting and supine subjects during three phases of flight: hypergravity (phase I), early microgravity (phase III), and late microgravity (phase IV). Heart rate declined 6% (P < 0.001) and right ventricular inflow velocities rose (46%, early;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…While meanRR is different between standing and supine subjects in normogravity and hypergravity, these differences disappear in microgravity. Johns et al (1994) found no differences in the supine position for cardiac filling and heart rate during different phases of parabolic flight suggesting that the underlying autonomic tone was maintained.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…While meanRR is different between standing and supine subjects in normogravity and hypergravity, these differences disappear in microgravity. Johns et al (1994) found no differences in the supine position for cardiac filling and heart rate during different phases of parabolic flight suggesting that the underlying autonomic tone was maintained.…”
Section: Discussionmentioning
confidence: 77%
“…During microgravity the central blood volume increased, which caused accumulation of the blood into the head and thorax (Johns et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, these changes are not accompanied by an increase in central venous pressure or AP. Buckey et al [5] and Foldager et al [6] measured central venous pressure during space flight, and found that it promptly dropped on entry into G. Despite the decrease in central venous pressure, the left atrial diameter, end-diastolic left ventricular volume, and cardiac output increase during G [5,7,8]. Thus, the central venous pressure might not reflect the cardiac filling pressure during exposure to G. To understand this discrepancy, the TP has to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…in fact, as a consequence of changes in hydrostatic pressure gradients in a standing position, acute variations in gravity induce dramatic fluid shifts from the lower extremities of the body towards the head and thorax, altering central filling volumes and pressures and resulting in significant cardiovascular effects (BAILLIART et al, 1998;LATHERS et al, 1989;MUKAI et al, 1994;NORSK et al, 1987). These modifications, together with changes in the sympathetic activity (heart rate and inotropic status), influence LV dimensions and function (JOHNS et al, 1994).…”
mentioning
confidence: 99%